Dietary Steamed Tomato Inhibits Hyper-production of Inflammatory Markers and Enhance miR-29b-3p Expression in Atherosclerosis Rats - Dafip, Muchamad; Iswari, Retno Sri; Kartika, Aprilia Indra; Reki, Winarto; Gasem, Muhammad Husein; Fitria, Meutia Srikandi (Universitas Negeri Semarang, 2024)
Atherosclerosis is triggered by cholesterol accumulation in endothelial layers that induces the production of inflammatory cytokines, including TNF-α, IL-6, and IL-10. This condition disrupts microRNA homeostasis like miR-29b-3p, generally maintaining artery health. Steamed tomatoes contain higher antioxidant properties than raw, which might be better against atherosclerosis. However, its influence on inflammation and miR-29b-3p balance remains unclear. This study aims to elucidate the effect of steamed tomatoes on the TNF-α, IL-6, and IL-10 levels and miR-29b-3p expression under atherosclerosis conditions. Sprague Dawley male rats were equally divided into K1 group of healthy rats given a placebo; K2 group was atherosclerosis rats induced with 2 m of cholesterin/ 200 g/KgBW per day, then K3 and K4 groups were atherosclerosis rats supplemented with 20 mg/ 200 g/KgBW per day of atorvastatin and 16 mg/ 200 g/KgBW per day of steamed-tomato extract for 60 days. Steamed tomato decreases cytokine level in the K4 group and significantly differs from all groups (p < 0.050). This study showed that increased proinflammatory cytokine, including TNF-α and IL-6, is hypothetically involved in plaque formation and lamina layer destruction in endothelial. Steamed tomato supplementation also significantly increases miR-29b-3p expression to 0.98 ± 0.33 log10 fold change higher than K2 and K3 (p = 0.000). This study demonstrated the potential of steamed tomatoes to improve dyslipidemia, atherosclerosis-related inflammation, and miRNA homeostasis. This research provides additional knowledge regarding determining the expression of miR-29b-3p, which has the potential to be developed as a diagnostic or therapeutic target.